The Level of teachers, practice of the first cycle of basic education in the development the values of citizenship among pupils (A Field Study In the city of Lattakia) - Barakat, Ghassan; Ali, Wafegah; Younies, Huda (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aimed to recognize The level of teachers practice of the first cycle of basic education in the development the values of citizenship among pupils in the city of Lattakia, and to recognize the difference between the averages of the responses the teachers on the questionnaire according to the variable of scientific qualification, to achieve the aim of the study, the research developed a questionnaire included (30) sentenses, and he applied on a random sample of (171) teachers. the study introduced recommendations about the role of teacher. By depending on the suitable statistic ways and using the approach of synthesis, the study found that the role of teacher in the development of values of citizenship among pupils from the point of view of teachers of the first cycle of basic education was high level, the role of teacher in the development of duties was the first, then belonging, then rights. the results have showed differences the averages of the responses the teachers on the questionnaire according to the variable of scientific qualification. هدف هذا البحث تعرُّف مستوى ممارسة معلمي الحلقة الأولى من التعليم الأساسي لدورهم في تنمية قيم المواطنة لدى تلاميذهم في مدينة اللاذقية، وتعرُّف الفروق بين متوسطات درجات إجابات أفراد العينة على الاستبانة تبعاً لمتغير المؤهل العلمي والتربوي, ولتحقيق الهدف من البحث تم إعداد استبانة تضمنت (30) بنداً موزعة على (3) محاور, وتم تطبيقها على عينة مكونة من(171) معلماً ومعلمةً, تم اختيارهم بالطريقة العشوائية البسيطة, واعتمد البحث المنهج الوصفي, وتمّت معالجة البيانات باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية والتربوية, ومن ثم مناقشة النتائج وتفسيرها, وصولاً إلى عدد من المقترحات. وأظهرت نتائج البحث أن مستوى ممارسة معلمي الحلقة الأولى من التعليم الأساسي لدورهم في تنمية قيم المواطنة لدى تلاميذهم كان مرتفعاً وعلى جميع المحاور، وكان أعلاها لدور المعلمين في تنمية قيم الواجبات بالترتيب الأول يليه قيمة الانتماء بالترتيب الثاني، ثم قيم الحقوق بالمرتبة الثالثة، وتبين وجود فروق بين متوسطات درجات إجابات أفراد العينة تبعاً لمتغير المؤهل العلمي والتربوي لصالح معهد إعداد معلمين.